Eksistensi Pendidikan Islam Dalam Menghadapi Perkembangan Ilmu Pengetahuan Dan Teknologi (Iptek) - Rumina Rumina (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2019)
Education as a learning activity or teaching and learning process can occur both inside and outside, as an educational activity can take place in the family, as well as in official educational institutions, activities or institutions are able to instill and make Islam as the basis for implementing education. The strategy implemented in facing the development of science and technology is the motivation of students' creativity towards the development of science and technology itself where Islamic values become a source of reference, educating skills, utilizing science and technology products, creating a strong link between religion and science and relationships with scientists who hold science and technology authority in their respective fields, Instill broad attitudes and insights into the future of humanity through the ability to interpret religious teachings. One of the priorities of national education development in relation to the development of the quality of human resources is related to improving the quality of each type and level of education so the existence of Islamic education in the face of the development of science and technology needs to be developed policies that emphasize improving the quality of human resources, intellectual intelligence, emotional intelligence, and spiritual intelligence.